Pengaruh Suhu Permukaan Laut Musiman terhadap Produksi Penangkapan Ikan Lemuru (Sardinella lemuru) di Perairan Selat Bali, Maret 2011 – Februari 2015 - A. A. Md. Ananda Putra Suardana; I Dewa Nyoman Nurweda Putra; Elok Faiqoh (Fakultas Kelautan dan Perikanan Universitas Udayana, 2021)
Lemuru fishing activity in the Bali Strait is the most dominant fishery sector in that waters. One of the environmental factors that affect lemuru is Sea Surface Temperature (SST) spread seasonally. One Remote Sensing technology that can be used in determining the value of the distribution of SST is Moderate Resolution Imaging Spectroradiometer (MODIS). This study aimed to explore the influence of SST on the production of lemuru fishing (Sardinella lemuru) in the waters of the Bali Strait each seasonally. The method used in this research is descriptive qualitative by look influence between SST seasonally to the production of lemuru fishing at Bali Strait. This study used correlation and regression polynomial equation. The results showed influence of SST seasonally to the production of lemuru fishing in west season amounted to 54.86% (proportional), in east season by 43.88% (inversely), in the transitional seasons I amounted to 37.05% (proportional), and on the intermediate season by 30.64% (proportional). The weak impact of SST on the production of lemuru fishing in the waters of the Bali Strait in every season caused by state of the SST is relatively constant, while the production of fishing lemuru in annually increasing.